Amerindinis perspektyvizmas ir pirmojo asmens perspektyvos įveika. - Šatkauskas, Ignas (Problems / Problemos, 2022)
The paper considers a polemic thesis that Viveiros de Castro's Amerindian perspectivism is characterized by the overcoming of the first-person perspective. Multi-natural cosmological deictic figures instead of the first-person perspective. This opposes the latter to the perspective of transcendental philosophy. The thesis of multiple worlds is an interpretation of the indigenous perspective which is determined, among other themes, by its point of view toward the West. It implies that Amerindian perspectivism should be understood as resistance to naturalism, akin to phenomenology's origin as it is conceived in eco-phenomenology. The ontological turn of anthropology is the most concerted attempt to formulate an anthropological version of Husserl's reduction that reduces the division of first and third-person perspectives to reveal the indigenous cosmological deictics. The opponents of the ontological turn oppose it to phenomenology.